“Urbs Aeterna” and Dutch Painting of Roman Ruins - Levine, David A. (Medieval Renaissance Baroque: a cat's cradle for Marilyn Aronberg Lavin, 2010)
"Reflects Marilyn Aronberg Lavin's innovative work in art and cultural history in both the print and digital realms. Contributors: Kirk Alexander, Horst Bredekamp, Nicola Courtright, David Freedberg, Jack Freiberg, Marc Fumaroli, David A. Levine, Daniel T. Michaels, Elizabeth Pilliod, Debra Pincus, Gary Schwartz. Seventy-seven illustrations, bibliography of Lavin's works, index"–Provided by publisher.
OCLC: 423389186
Keywords: dept.art